Evaluasi Aspek Fungsi Pohon dan Perdu Hutan Kota Velodrome Malang - Wilhelmus Boli Waton; Rizki Alfian (Universitas Mulawarman, 2022)
AbstrackEvaluation of Functional Aspects of Trees and Shrubs in Malang Velodrome City Forest Malang City has green open space with a total area of ​​1752.15 ha of green open space which is divided into 33.56 ha of urban forest, 175.49 ha of city parks, 59.19 ha of field, 218.64 ha of green lanes, 1102.43 ha of river borders, and other forms of 162.84 ha (Ministry of Public Works 2012). Malang City area in 2012 was recorded as having urban forest of 0.35% of the total area of ​​Malang City. One of the green open spaces that became the reason for the research is the Malang Velodrome City Forest. This urban forest is in the form of spreading and piling up. Plants found in this urban forest are the main elements studied by researchers, so plants that have a beautiful and functional visual appearance provide physical benefits so that they can meet the physical and spiritual needs of the visitors. Planting plants sometimes develop into a specific function, for example, as a fence to reduce the effects of wind.This study aims to analyze the quality of plants in terms of function according to the criteria in the science of landscape architecture. The basis for assessing plant function is done by comparing the criteria for plant function that should be with conditions in the field. The results of this study are expected to add information to landscape architecture, planners, and managers to consider aspects of physical function in the development of landscape plants.Keywords: Urban Forest, Landscape plant function